ARRIVAL ORDER AND AQUATIC MACROPHYTE COMMUNITY ORGANIZATION IN A TROPICAL ESTUARY - Nunes, Laís Samira Correia [UNESP]; Camargo, Antonio Fernando Monteiro [UNESP] (Oecologia Australis, 2022)
The arrival order in species colonization may be important to the communities’ organization of perennial plants along environmental gradients. In estuarine gradients, the competitive exclusion may have great importance to species zonation regardless of their arrival order. However, priority effect has also been considered, since founder species may remain in the environment even with the later arrival of species of greater competitive ability. We evaluated whether the arrival order and priority effect influence the interspecific interaction between adult individuals (early-colonizing individuals) and young individuals (later-arriving individuals) of the perennial emergent estuarine aquatic macrophytes Spartina alterniflora (S) and Crinum americanum (C). We conducted a laboratory experiment with four cultures (monocultures of early-colonizing individuals of S; monocultures of early-colonizing individuals of C; cultures of early-colonizing individuals of S with introduction of later-arriving individuals of C; and cultures of early-colonizing individuals of C with introduction of later-arriving individuals of S) and two sediment types (lower and middle estuary sediment: salinity 32 and 20, respectively). We hypothesized that, due to the priority effect, in both sediment types (i) the later-arriving species would not establish itself in adult early-colonizing vegetation and (ii) the later-arriving species would not limit the growth of the early-colonizing species. Our results corroborate our hypotheses as the later-arriving individuals of S. alterniflora and C. americanum did not grow up and establish themselves in the heterospecific cultures of early-colonizing individuals in both sediment types. Furthermore, the growth of the early-colonizing individuals was not limited by the presence of the later-arriving individuals. We conclude that the arrival order and priority effect can influence the interspecific competition, communities’ organization and spatial distribution of aquatic macrophytes in tropical estuaries.
Keywords: colonization; competitive exclusion; Crinum americanum; environmental gradient; Spartina alterniflora